Characterising the role of circulating immune cells in brain metastasis - Balathasan, L (2012)
Brain metastasis is a frequent occurrence in cancer patients and carries a high mortality rate. The incidence of brain metastasis is on the rise, highlighting the need for improved therapeutic intervention. Immune cells have been shown to promote disseminated tumour cells to colonise the lung and liver. Therefore, we aim to determine whether immune cells also facilitate brain metastasis by describing the host immune response to tumour cells attached to the brain vasculature. We developed a model of brain metastasis by using ultrasound guidance to perform intracardiac injection of tumour cells. Using this method, we identified highly and weakly brain metastatic cell lines. To understand how cancer cells develop into brain metastases, we analysed brains harvested 4 h- 14 d after tumour injections. At 4 h after intracardiac injection, only cell lines that developed into brain metastases were found adhered to the brain vasculature in high numbers. A small number of arrested tumour cells clustered with CD45⁺ immune cells. These tumour-CD45 clusters persisted over time whilst the frequency of solitary tumour cells declined. Tumour-associated CD45⁺ immune cells were identified to be Ly6G⁺Gr-1⁺CD11c⁻ myeloid cells. Considerably more tumour-CD45⁺ immune cell clusters were found within the brain vasculature when tumour cells were injected into mice bearing a primary tumour. Increased tumour-CD45⁺ immune cells clusters correlated with an increased number of brain metastases in the same group of mice. We also found a positive association between increased tumour-immune clusters and levels of tumour and host derived G-CSF. To establish a causal relationship between tumour cell-CD45 clusters and metastases, we developed an experimental setup for transcranial imaging. Our results suggest that tumour recruited immune cells may promote tumour cell colonisation of the brain and provides a framework for further investigation.